Factors associated with symptom relief in patients with irritable bowel syndrome: a retrospective cohort study - Zhao, Ming; Luo, Rui; Shen, Yang; Zhang, Youjian; Dong, Jiaqi; Lv, Muhan (Frontiers in Medicine, 2025)
BackgroundSymptom relief in irritable bowel syndrome (IBS) varies widely, influenced by demographic, clinical, and psychosocial factors. Identifying factors associated with symptom relief can enhance management strategies for IBS patients.ObjectiveThis study aimed to examine factors associated with symptom relief in a cohort of IBS patients, focusing on the role of demographic, lifestyle, psychological, and physiological characteristics.MethodsWe conducted a retrospective cohort study of 278 IBS patients treated at a tertiary hospital. Demographic data, IBS subtype, symptom severity, lifestyle factors, and psychological variables (anxiety, depression, stress) were collected. Symptom relief, defined as a 50% reduction in baseline symptom severity, was the primary outcome. Univariate and multivariate logistic regression analyses were performed to identify factors associated with symptom relief, with subgroup analyses examining key demographic and lifestyle factors.ResultsIn multivariate analysis, symptom severity (OR = 1.20, 95% CI: 1.05–1.37, p = 0.008), daily exercise (OR = 1.50, 95% CI: 1.01–2.24, p = 0.04), and low depression scores (OR = 0.93, 95% CI: 0.89–0.98, p = 0.003) remained independent predictors of symptom relief.ConclusionSymptom severity, daily exercise, and lower depression levels are independently associated with symptom relief in IBS patients, highlighting the importance of lifestyle modifications and mental health support. These findings suggest that physical activity and psychological well-being were associated with symptom relief, highlighting their potential relevance in holistic IBS management strategies.